Occurring of In Vitro Functional Vasculogenic Pericytes from Human Circulating Early Endothelial Precursor Cell Culture - Silvia Cantoni; Francesca Bianchi; Margherita Galletti; Elena Olivi; Francesco Alviano; Nazzareno Galiè; Carlo Ventura (Hindawi Limited, 2015)
Pericytes are periendothelial cells of the microcirculation which contribute to tissue homeostasis and hemostasis by regulating microvascular morphogenesis and stability. Because of their multipotential ex vivo differentiation capabilities, pericytes are becoming very interesting in regenerative medicine field. Several studies address this issue by attempting to isolate pericyte/mesenchymal-like cells from peripheral blood; however the origin of these cells and their culture conditions are still debated. Here we showed that early Endothelial Progenitor Cells (EPCs) expressing CD45+/CD146+/CD31+ can be a source of cells with pericyte/mesenchymal phenotype and function, identified as human Progenitor Perivascular Cells (hPPCs). We provided evidence that hPPCs have an immunophenotype consistent with Mesenchymal Stem Cells (MSCs) from human adipose tissue (hASCs) and fetal membranes of term placenta (FM-hMSCs). In addition, hPPCs can be subcultured and exhibit expression of pluripotent genes (OCT-4, KLF-4, and NANOG) as well as a remarkable vasculogenic potential. Our findings could be helpful to develop innovative cell-based therapies for future clinical applications with distinct therapeutic purposes.